Fully printed, stretchable and wearable bioimpedance sensor on textiles for tomography. (25th February 2021) - Jose, Manoj; Lemmens, Marijn; Bormans, Seppe; Thoelen, Ronald; Deferme, Wim
Abstract: Electrical impedance tomography (EIT) is a non-invasive, real-time, continuous imaging technique that has multiple applications in health care. EIT is a realizable technique for radiation-free medical imaging ranging from real-time monitoring of bone fracture repair to lung functioning. This work explores the prospect of printing a wearable bioimpedance sensor on textiles for EIT imaging. Screen printing and stencil printing were applied to fabricate the sensor on the textile substrate and the imaging was carried out with the worn sensor on the human body. The first part of this work focuses on developing a flexible textile sensor in the form of a bracelet to obtain cross-sectional images of the forearm that unravel bone features like shape, size and position. However, body parts such as the thorax have added complexities due to their constantly varying perimeter and uneven shape. It is a significant prerequisite for the wearable sensors to apply to dynamic body parts where irregular shape and continuous volume variations occur. The second part of the paper therefore addresses the fabrication and testing of a stretchable textile-based sensor to address such instances of body dynamicity. The proposed stretchable sensor, worn on the thorax, demonstrates the feasibility of imaging such an uneven and dynamic body part. Although the EIT images are inherently attributed to low resolution, this work shows the prospect of wearable imaging applications in health monitoring. Apart from demonstrating the printed sensor for EIT imaging, this paper shows the image rendering quality dependency over the frequency of the signal and the number of electrodes. This work could initiate further research on wearable EIT based health monitoring devices for real-life scenarios.